Targeting TIGIT Inhibits Bladder Cancer Metastasis Through Suppressing IL-32 - Wu, Kang; Zeng, Jun; Shi, Xulian; Xie, Jiajia; Li, Yuqing; Zheng, Haoxiang; Peng, Guoyu; Zhu, Guanghui; Tang, Dongdong; Wu, Song (Frontiers in Pharmacology, 2022)
Bladder cancer is a highly metastatic tumor and one of the most common malignant tumors originating in the urinary system. Although the application of immune checkpoint, including programmed cell death-1 (PD-1) and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4), achieved definite efficacy, the effect of immunotherapy for bladder cancer is still not very satisfactory. Therefore, it is very urgent to develop new targets to expand the options of immunotherapies. In this study, we utilized single cell sequencing to explore the cell composition and detected a subset of Treg cells with high expression of T cell immunoreceptor with immunoglobulin and immunoreceptor tyrosine-based inhibitory motif domain (TIGIT) and interleukin (IL)-32 molecules. Certainly, anti-tumor immune response was suppressed by this subset of Treg cells and IL-32 promoted the bladder cancer metastasis. Nevertheless, targeting TIGIT not only could reverse immunosuppression through restoring anti-tumor immune response mediated by T cells but suppressed the secretion of IL-32 and inhibited the metastasis of bladder cancer cells. Thus, our study provided a novel insight into the immunosuppression in bladder cancer and developed the TIGIT as the novel target for immunotherapy of bladder cancer. Furthermore, we also illustrated mechanism of the dual effect of targeting TIGIT in bladder cancer and revealed the metastasis-promoting effect of IL-32 in bladder cancer. Taken together, the discovery raises the possibility of TIGIT targets against bladder cancer from the bench to the bedside.